Tourism Potential and the Role of Tourism Communication in Developing Community-Based Ecotourism: A Case Study of Edelweis Park, Besakih Village, Bali - Surya Sidhanta, I Nyoman Windu; Nina Eka Lestari, Ni Putu (Jayapangus Press, 2025)
Tourism supports the agricultural and industrial sectors, on which Bali's income and economic growth depend. The presence of tourism is an alternative industry in improving the economic welfare of people in rural areas. The Covid-19 pandemic has had a major impact on economic, socio-cultural, and environmental aspects, including tourism in Bali Province. The objectives of this research are preparing a basic study on the potential of tourist objects and objects as well as the readiness of the participation of the people of Besakih Village in the model of developing tourist destinations of Edelweis Park as Community-Based Ecotourism and to find out tourism communication in introducing and developing community-based ecotourism in the tourist attraction of Edelwiss Park, Besakih Village. This research is a type of Action research. The type of data to be used is perception data and existing data, allowing a quantitative approach in the form of qualitative descriptive analysis to examine the general description, demographics, and socio-economic characteristics of Besakih Village. The results of this study show that: (1) the results of the assessment of the elements of attraction of Edelweis Park tourist attractions, namely aspects of tourist attractions, accessibility, socioeconomic environmental conditions, accommodation, and supporting infrastructure, the average value of the assessment of the attractiveness of Edelweis Park tourist attractions is included in the category of quite potential; (2) Local governments and tourism destination managers need to design a tourism communication strategy that includes optimizing digital promotion, developing content based on local wisdom narratives, and utilizing visual media to attract tourists and convey messages related to conservation efforts.